Reproducibility in the cardiometabolic responses to high-intensity interval exercise in adults with type 1 diabetes. (February 2019) - Riddell, Michael C.; Pooni, Rubin; Yavelberg, Loren; Li, Zoey; Kollman, Craig; Brown, Ruth E.; Li, Aihua; Aronson, Ronnie
Highlights: The cardiometabolic response to HIIT in persons with T1D was highly reproducible. There was a significant increase in glucose following HIIT in the fasted state. Variability in the glucose response to HIIT was correlated with increased lactate. Hyperglycemia following HIIT is a challenge for T1D management. Abstract: Aims: Patients with type 1 diabetes (T1D) often report a rise in their blood glucose level following brief intense exercise. We sought to determine the reproducibility of the cardiometabolic responses to high-intensity interval training (HIIT). Methods: Sixteen adults with T1D, using an optimized multiple daily injection with basal insulin glargine 300 U/mL (Gla-300), performed four fasted HIIT sessions over a 4–6-week period. Exercise consisted of high-intensity interval cycling and multimodal training over 25 min. Results: Heart rate and rating of perceived exertion rose similarly in all sessions, as did lactate, catecholamine and growth hormone levels. Plasma glucose increased in response to HIIT in 62 of 64 visits (97%), with an overall increase of 3.7 ± 1.6 mmol/L (Mean ± SD) (P < 0.001). In within-patient comparisons, the change in plasma glucose among the four HIIT sessions was significantly correlated with a composite correlation of 0.58 ([r 2  = 0.34]; 95% CI 0.35–0.80; P  < 0.01). Conclusions: Intersession observations of four separate HIIT sessions showed high intrasubject reproducibility in the cardiometabolic responses to exercise, including the rise in plasma glucose, when adults with T1D perform the activity in a fasted state.